Conflicting Interest in the Production of Wind Energy: Public Demand for Shores without Wind Turbines - Müürsepp, Margot; Ehrlich, Üllas (Estonian Discussions on Economic Policy, 2013)
In contrast to countries with longer experience in the field, Estonia has not actively included public opinion into the planning process of new wind farms. Wind farms in Estonia are built mainly on the coast, 90% of which is covered with natural surface. The paper investigates, using the Contingent Valuation Method (CVM), the willingness of Estonian inhabitants to pay for preserving the Estonian coastal zone wind turbines free. Total demand of Estonian adult population for Estonian shores in their natural condition without wind turbines is found to be considerable 23.4 million euro annually. The demand of the population for the preservation of the nature underlines the need for changes in national strategies for the wind power sector.